Driving factors of the Collaborative Consumption in the European Union scene - María Barreiro-Gen (Atlantic Review of Economics (ARoEc), 2018)
The defense of unlimited economic growth as the main objective to be achieved has been questioned for decades and with even more intensity in recent years. In this context, the Sharing Economy's initiatives have dramatically increased. This study expands our current understanding of driving factors of the Collaborative Consumption in European Union member countries, focusing on the case of Spain. A cluster analysis was run, involving two methods: the hierarchical and the iterative. The results obtained were compared with the available scarce data and the position of the main stakeholders. The analysis has shown that the northwest in Europe is the best position to develop activities as part of a Sharing Economy. However, data have shown that there are countries as Spain, in the southwest, with a lot of initiatives: the consequences of the economic crisis and the need to save money have been shown as the main drivers of these new models of business in these states. On the other hand, the favorable attitude of the institutions of the European Union to the Collaborative Economy has to be highlighted and its rejection of increased regulation that would hinder its development.
Keywords: D10; D20; D40; D60; O10; O33; 330; Business; consumption; e-commerce; economic; ICT; sustainable